A generalised failure envelope for undrained capacity of circular shallow foundations under general loading. Issue 3 (14th July 2014) - ,; ,; Gourvenec, S
Abstract : This paper presents a generalised failure envelope for the prediction of the undrained capacity of circular shallow foundations under general vertical, horizontal and moment (VHM) loading. Uniaxial capacities and failure envelopes under combined loading are presented for shallow circular foundations over a practical range of embedment ratio and soil strength heterogeneity. An approximating expression is proposed to describe the shape of the normalised VHM failure envelope as a function of foundation embedment ratio, normalised soil strength heterogeneity index and vertical load mobilisation.